Utilization of Waste Glass Powder and Glass Composite Fillers in Asphalt Pavements - Jayvant Choudhary; Brind Kumar; Ankit Gupta (Advances in Civil Engineering)
Today, researchers around the globe are looking for suitable alternatives of conventional fillers which can form flexible pavements with satisfactory engineering performance in an environmental friendly and cost-effective manner. This study investigated the engineering, economical, and environmental viability of recycling waste glass powder (GP) and glass-hydrated lime (GL) composite as alternative fillers, in place of stone dust (SD). All fillers were characterized, and asphalt concrete mixes incorporating them at different proportions (4–8.5%) were designed using the Marshall mix design method. The engineering performance of asphalt mixes was analyzed using the static creep analysis, indirect tensile fatigue test, Cantabro test, modified Lottman test, resilient modulus test, mixing time analysis, and boiling water test. Additionally, the design of single km of two-lane flexible pavements utilizing aforesaid mixes was done as per the mechanistically empirical method suggested in IRC 37 guideline. Finally, the economic and environmental analysis was done by comparing their material cost and global warming potential (GWP). GL and GP mixes exhibited better resistance against rutting, fatigue, and low temperature cracking at lower optimum asphalt content than SD mixes. However, GP mixes also displayed poor moisture resistance and adhesion due to the high amount of silica in GP. GL mixes had satisfactory moisture resistance up to 7% filler content due to the fine nature and anti-stripping properties of hydrated lime. The pavement containing GL and GP fillers also reduced material cost and GWP up to 35% while consuming up to 74 tons of GP.